Profitability Moderates The Effect Of Capital Structure And Dividend Policy On Stock Returns - Alfina Alfina; Sufirna Nofri Yanti, Akhmad Akram Hirman, Addini Alifa Anwari (Pascasarjana STIE Amkop Makassar, 2026)
This study examines the stock returns of pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2023, focusing on the moderating role of profitability in the relationship between capital structure, dividend policy, and stock returns. The research employs a quantitative approach using secondary data sourced from the Indonesian Stock Exchange. Data analysis was conducted using SPSS version 26, applying multiple linear regression and moderated regression analysis (MRA).The findings reveal that capital structure has a positive and statistically significant effect on stock returns. In contrast, dividend policy exhibits a negative but statistically insignificant effect on stock returns. Profitability moderates the relationship between capital structure and stock returns, weakening its impact. However, profitability does not moderate the relationship between dividend policy and stock returns.These findings provide valuable insights for managers and investors in making informed investment decisions.